Correction: Zonta et al. Melatonin Reduces Angiogenesis in Serous Papillary Ovarian Carcinoma of Ethanol-Preferring Rats. Int. J. Mol. Sci. 2017, 18, 763 - Zonta, Yohan Ricci [UNESP]; Martinez, Marcelo; Camargo, Isabel Cristina Cherici [UNESP]; Domeniconi, Raquel Fantin [UNESP]; Lupi Júnior, Luiz Antonio [UNESP]; Pinheiro, Patricia Fernanda Felipe [UNESP]; Reiter, Russel J.; Martinez, Francisco Eduardo [UNESP]; Chuffa, Luiz Gustavo de Almeida [UNESP] (MDPI, 2025)
In the original publication [...].